(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2024)
This article discusses the process of scenic creation “Corpo-Alvo: Poética e Singularidade de um Corpo Preto Entre-Lugares” that is part of the show “Bagagem de Desjeitos”, resulting from the Theater course at the Federal University of Tocantins. The objective is to problematize issues of race/racism inflicted on black bodies in a structural way. The theoretical framework was constructed based on studies in African cosmological philosophy and research in theater. It is concluded that the performing arts can enhance the problematization of racism/racialization in black bodies, as theatrical praxis allows the director and/or performer to investigate the silencing impulses that hinder their existence.